Medidas de adaptação de mudanças climáticas à luz da justiça climática: um estudo de caso da megacidade de São Paulo - Calderon, Adelia Judith (2022)
The present case of study seeks to situate the city of São Paulo in the global climate debate in order to analyze, in the light of climate justice, the current and future impacts relate to climate change, focusing mainly on impacts on vulnerable populations, especially regarding women, black, poor and indigenous people. In order to demonstrate the transversality of the issues related to climate justice, parallels were made between this theme and aspects of social participation and urbanization. The main public instruments in force on climate adaptation in the municipality were mapped and studied, in order to understand whether climate justice is contemplated in them, understand the demands of the city to the subject, identify the proposed plans and their own efforts for its materialization, continuity and concreteness, and finally, investigate and reflect on unfilled gaps and possible points for improvemen